Nuclear structure aspects of the heaviest N∼Z nuclei south of 100Sn. (1st March 2023) - Górska, M.; Albers, H. M.; Arici, T.; Banerjee, A.; Benzoni, G.; Blazhev, A.; Cederwall, B.; Das, B.; Davinson, T.; Gerl, J.; Grawe, H.; Hall, O.; et al.
Abstract: Ever-lasting interest in the structure of 100 Sn and neighbouring nuclei is still well justified by the fact that it is the heaviest doubly-magic nucleus with N=Z. State-of-the-art experimental techniques involving stable and radioactive beam facilities have enabled access to these exotic nuclei. In particular, the analysis of experimental data obtained in two DESPEC experiments at GSI Darmstadt extends the information on the shell structure and its evolution towards N = Z = 50, and allows the study of seniority conservation and proton-neutron interaction in the g9/2 orbit. Several theoretical approaches for shell-model investigations are discussed and their predictive power assessed. The calculated systematics of the reduced transition probabilities for high- to medium-spin states in N∼Z isotopes with active g9/2 orbit is presented for the first time.